The Oxford handbook of the Egyptian book of the dead - Lucarelli, Rita; Stadler, Martin Andreas (Oxford handbooks online, 2023)
With a generous, thorough selection, editors Rita Lucarelli and Martin Andreas Stadler offer in 'The Oxford Handbook of the Egyptian Book of the Dead' a wide-ranging synthesis of essential scholarship on Egyptian religious and mystical practices, centered on the central text of that tradition.